THE SILENCING OF QUEER VOICES IN THE LITIGATION OVER TRINITY WESTERN UNIVERSITY’S PROPOSED LAW SCHOOL - Hamill, Sarah; Feinstein, Pippa (Windsor Yearbook of Access to Justice / Recueil annuel de Windsor d'accès à la justice, 2017)
This article assesses to what extent the recent litigation over the accreditation of Trinity Western University’s proposed law school includes and considers queer voices. We argue that a close examination of how queer people’s voices appear in these decisions reveals that when queer voices are absent or marginal, queer people’s rights are mischaracterized. In turn the mischaracterization and misunderstanding which flows from the failure to properly include queer voices hinders the ongoing struggle for queer equality. We rely on discourse analysis to make our argument. We argue that Canadian courts should seek to ground their decisions relating to queer equality in the lived experiences of queer people. Here we argue that Justice L’Heureux-Dubé’s dissent in Trinity Western University v British Columbia College of Teachers offers a good blueprint for future decisions to follow as they engage with queer equality.